Interior Design of Smart Home Based on Intelligent 3D Virtual Technology - Wei Liu (International Journal of Informatics and Information Systems, 2022)
With the development of society and the continuous advancement of technology, people's research on smart home products is gradually deepening. Compared with the past, smart homes are no longer out of reach, but actually penetrate into our lives. However, while continuously exploring the technology of smart home products, designers have not conducted in-depth research on the interactive mode of the control interface of smart home products. Based on this, the purpose of this article is to study the smart home interior design based on intelligent three-dimensional virtual technology. This article first analyzes the development and current situation of smart homes, and on this basis, combines three-dimensional virtual reality technology to research and analyze smart home systems (S H S). This article systematically elaborates the design of functional modules of the S H S based on intelligent 3D virtual reality technology and the method of converting 2D plane to 3D space coordinate. And use comparative analysis method, interview method and other research methods to carry out experimental research on the theme of this article. The research shows that compared with the traditional S H S, the S H S based on 3D virtual technology studied in this paper has higher feasibility.